Balancing Scale of Washback Effect of English Language Assessment in Junior High School Level: A Literature Review - Nurjati, Nunung; Rahayu, Endang Mastuti (Universitas PGRI Adi Buana Surabaya, 2023)
The washback effect of English language assessments in junior high school has been a topic of debate among educators and researchers. While some argue that these assessments can have positive effects on students' learning, others suggest that they may have negative consequences. This article explores the washback effect of English language assessments at the junior high school level, examining both the positive and negative impacts. The study employs a review on predefined related literatures. The findings suggest that while English language assessments can have positive effects on students' motivation and study habits, they may also lead to teaching to the test and a narrow focus on assessment criteria. The article concludes with recommendations for improving the design and implementation of English language assessments to minimize negative washback effects.